PENGARUH PENGGUNAAN ASBUTON BUTIR T.5/50 UNTUK PERKERASAN ASPAL SMA (STONE MATRIX ASPHALT) - novia anggraini anggraini; Winayati Winayati; Hendri Rahmat (LPPM Universitas Abdurrab, 2021)
The highway as one of the means of land transportation, its usefulness is felt to be increasingly important to increase the improvement of the national economy. One solution to build this road is to try the use of SMA (Stone Matrix Asphalt) asphalt pavement. Stone Matrix Asphalt (SMA) is asphalt concrete with a hot mix consisting of coarse aggregate, fine aggregate, filler material and binder (asphalt). The purpose of the study was to determine the effect of using Asbuton grain T.5/20 for asphalt pavement of the Asphalt Stone Matrix on Marshall characteristics. The materials used in the mixture are coarse aggregate from the base, fine aggregate, asphalt pen 60/70 and asbuton grain T.5/20 originating from Buton Island, Southeast Sulawesi. Marshall test for asphalt matrix asphalt on aggregate mixture with asphalt content of 4.5%, 5%, 5.5% and 6% obtained the optimum asphalt content value of 5.75%. After obtaining the optimum asphalt content, modifications were made by adding asbuton grain T.5/20 to the aggregate mixture as much as 2%, 2.5%, and 3%. The more use as a grain in the mixture, the higher the value obtained. Stability is an indicator of pavement strength under traffic loads. Asphalt Stone Matrix which is designed to obtain a large void content, while the proportion of VMA cavities obtained is getting smaller and does not meet the specification requirements.__